Abs. Issue 1 (November 2015) - Meshalkina, D.; Shevtsov, M.; Margulis, B.; Guzhova, I.
Abstract : Glioblastoma is one of the most malignant cancer types. Its median survival is 15 months with combined radio- and chemotherapy and only 4 months without therapy. Molecular chaperones play a very multifaced role in tumor development. Depletion of Hdj1 in cancer cells accelerates tumor growth. Decrease of Hdj2 level correlates with the increase of tumor aggressiveness, but also attenuates tumor protection against radiotherapy. Hsp70 provides considerable survival advantages to the cancer cells, but at the same time can act as a "chaperokine", activating antitumoral immunity. For assessment of chaperone's role in glioma progression, invasiveness and metastasis formation we chose rat model of intracranial injection of 10 5 C6 cells. We developed three C6-based cell lines with protein knock-down by RNA-interference: C6 shHsp70 (on 83%), C6 shHdj1 (on 96%) and C6 shHdj2 (on 52%). The last differed in roundish and easily detachable morphology. Following intracranial injection of the modified tumor cells, the animals' survival was estimated. As compared to the groups of control C6 (25.4 ± 3.9 days) and C6 shHdj1 (25.5 ± 3.8) we observed a nearly 1.5-fold decrease in survival in C6 shHdj2 (16.8 ± 3.5 days) ( P  < 0.05). On the contrary, in C6 shHsp70 group the survival increased up to 42.5 ± 12.0 days (the increase is completely explainable by the slower growth rate of the culture). Subsequent MR imaging and histological analysis of tumors demonstrated elevated invasiveness and metastatic activity in C6 shHdj2 group in comparison to C6 shHsp70, C6 shHdj1 and control C6. High migration activity and the ability of floating C6 shHdj2 cells to adhere and settle on the substrate was proved in wound-healing assay, spot-healing assay, colony forming assay and transwell migration assay. Adhesion assay showed decreased adhesion ability of C6 shHdj2 cells and increased – of C6 shHsp70 cells on all types of tested extracellular matrixes. Immunofluorescence analyses showed loss of membrane- expressed N-cadherin and loss of intercellular contacts mediated by N-cadherin in C6 shHdj2 cells in comparison to other considered cell lines (although its level in western blot was elevated). Actin staining with rhodamine-falloidin revealed highly abundant leading edges in C6 shHdj2 culture. Matrix metalloprotease zymography proved an increased activity in gelatinases (mmp2 and mmp9) as well as in caseinases (mmp1 and mmp8) in C6 shHdj2 culture supernatant. Assay of stemness marker CD133 expression showed its 11.8 times increase in C6 shHdj2. Our experiments proved the high importance of Hdj2 level in glioma progression, invasion and metastasis.